Advanced Therapy Medicines Based on Oncolytic Viruses (Part I: Development and Authorisation of Products in China) - E. V. Melnikova; O. A. Rachinskaya; V. A. Merkulov (Регуляторные исследования и экспертиза лекарственных средств)
One of the promising areas in the development of innovative products for the treatment of cancer is the use of oncolytic (native or genetically modified) viruses (OLVs) for selective targeting of tumour cells and their destruction, especially as part of combination therapy. At present, there are three OLV-based products approved for medical use (two in China and one in the USА and EU). The aim of the study was to analyse data on specific aspects of OLV-based products’ development, preclinical and clinical research, and authorisation process in China. The authors analysed data freely available on the manufacturers’ websites, in public reports and documents of the Chinese regulatory authorities, in international clinical trial registries, and scientific publications. The products Gendicine® (SiBiono GeneTech Co., Ltd.) and Oncorine® (Shanghai Sunway Biotech Co., Ltd.) were originally developed and approved in China for clinical use as part of combination therapy. The analysis demonstrated long product development periods (Gendicine had been studied for 14 years before the start of the authorisation procedures), complex preclinical trial designs, and potential use of the products for several medical conditions with different tumour localisation. The identified specific aspects of OVL-based products’ development and authorisation in China could be taken into account in the regulatory practice of the Russian Federation.